Enhancing Project-Based Learning through Digital E-Modules in Elementary Schools - Haryanti, Yuyun Dwi Haryanti; I Gusti Agung Ayu Wulandari; Ni Ketut Desia Tristiantari; Ani Rosidah; Devi Afriyuni Yonanda; Minnatul Maula (Universitas Pendidikan Ganesha, 2025)
The development of technology in the world of education requires innovation in learning, one of which is the use of project-based digital teaching modules in elementary schools. Project-based learning, commonly called Project-Based Learning, has been shown to improve students' critical thinking skills, creativity, and collaboration. However, the implementation of project-based learning still faces obstacles, such as limited digital learning resources that suit the needs of teachers and student learning characteristics. This research aims to identify the need for the development of project-based digital teaching modules that can increase student engagement and understanding in the learning process. This research is qualitative descriptive with a needs analysis approach. Data collection through interviews, observations, and questionnaires to teachers and students in elementary schools involved 100 participants. Data analysis techniques through the process of data collection, data reduction, data presentation, conclusion drawn, and verification. The results of the study show that teachers need digital teaching modules that are interactive, easy to use, and support students' critical and collaborative thinking skills. Students are more motivated when using digital-based learning media that is challenging and engaging. The conclusion of this study emphasizes that the development of project-based digital teaching modules must pay attention to the needs of teachers and students, and be supported by adequate facilities and infrastructure in schools. These findings are the basis for the development of project-based digital teaching modules that are relevant to 21st century learning needs.